Incidental Detection of Malignant Melanoma Brain Recurrence on 68Ga–Prostate-Specific Membrane Antigen PET/CT. (November 2020) - Hod, Nir; Lantsberg, Sophie; Benkovich, Elya; Kazap, Dina Ezroh; Preiskel, Mark; Levin, Daniel
Abstract : Abstract: A 76-year-old man with a prior medical history of resected malignant melanoma of the skull underwent 68 Ga–prostate-specific membrane antigen (PSMA) PET/CT due to rising tumor markers of a known prostate carcinoma. Unexpected high 68 Ga-PSMA brain uptake was encountered around the surgical cavity in the skull with initially no specific structural changes on anatomical imaging. Successive CT and MRI eventually revealed local melanoma brain recurrence at this site. This interesting case demonstrates the diagnostic potential of 68 Ga-PSMA PET/CT imaging for detection of malignant melanoma brain recurrence.